2019
DOI: 10.1016/s2214-109x(19)30189-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of integrated interventions layered on mass drug administration for urogenital schistosomiasis elimination: a cluster-randomised trial

Abstract: Background Elimination of schistosomiasis as a public health problem and interruption of transmission in selected areas are targets set by WHO for 2025. Our aim was to assess biannual mass drug administration (MDA) applied alone or with complementary snail control or behaviour change interventions for the reduction of Schistosoma haematobium prevalence and infection intensity in children from Zanzibar and to compare the effect between the clusters. Methods In a 5-year repeated cross-sectional cluster-randomise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
139
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(142 citation statements)
references
References 29 publications
2
139
0
1
Order By: Relevance
“…To alleviate the need for ongoing treatment and to prevent resurgence, EOT is required after reaching EPHP 2,5,7 . The transition of treatment programmes from EPHP to EOT will require reassessment of the treatment strategy.…”
Section: Moving Towards Elimination Of Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…To alleviate the need for ongoing treatment and to prevent resurgence, EOT is required after reaching EPHP 2,5,7 . The transition of treatment programmes from EPHP to EOT will require reassessment of the treatment strategy.…”
Section: Moving Towards Elimination Of Transmissionmentioning
confidence: 99%
“…It is an intestinal or urogenital disease caused predominantly by Schistosoma mansoni or S. haematobium. Individuals become infected when cercariae, released by freshwater snails, penetrate the skin during contact with contaminated water 2 . The disease can result in anaemia, chronic pain, diarrhoea, and malnutrition, causing poor school performance and lower fitness 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Modelling studies have indicated that breaking transmission may theoretically be possible with mass preventive chemotherapy alone at high coverage and compliance 98,140 . Field studies and trials are currently underway to confirm if this is feasible in practice 141,142 . Moving towards elimination will likely require more intensive strategies, including treatment in low prevalence settings 14 .…”
Section: Evaluation Of Alternative Interventions and Strategiesmentioning
confidence: 99%
“…In this issue of Lancet Global Health, Knopp and colleagues' cluster randomised trial provides programmatic insight on how to implement integrated interventions with the goal of elimination of Schistosoma haematobium infection in an African setting with low prevalence (ranging from 4•2%-7•8%). 9 The study, done in Zanzibar, assessed the efficacy of three intervention strategies: biannual MDA with PZQ alone, biannual MDA in combination with snail control, or biannual MDA with PZQ and activities to Several interpretations and conclusions can be drawn from these results. Based on the results, a significant decline in the prevalence of S haematobium can be expected with biannual MDA with PZQ for 5 years without integrating other complementary measures in an area with a relatively low baseline prevalence of S haematobium.…”
Section: Participatory Integrated Control Strategies and Elimination mentioning
confidence: 99%